THE INFLUENCE OF SERVICE CONVENIENCE AND PRICE FAIRNESS ON CUSTOMER LOYALTY: MEDIATING EFFECT OF CUSTOMER SATISFACTION - Pinaraswati, Sandra Oktaviana; Farida, Ilya; Susilowati, Sri; Suprihati, Suprihati (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
The development of Indonesian apartments which have not fully recovered after the Covid pandemic is the reason for the need to increase sales. To increase sales, managers need to pay attention to Customer Loyalty from Apartment residents where Customer Loyalty is influenced by Service Convenience, Price Fairness, and Customer Satisfaction. The research objective is to analyze the effect of Service Convenience and Price Fairness on Customer Loyalty mediated by Customer Satisfaction. The population of this research is the occupants of the Tamansari Prospero Apartment in Sidoarjo as many as 200 people. The determination of the sample was carried out using the Slovin formula so that a total sample of 133 people was obtained. The research data collection technique was carried out by distributing questionnaires. While the data analysis technique uses Partial Least Square analysis. The results of the study prove that Service Convenience and Price Fairness have a significant effect on Customer Satisfaction. Customer Satisfaction has a significant effect on Customer Loyalty. In addition, Customer Satisfaction can mediate the effect of Service Convenience and Price Fairness on Customer Loyalty. Keywords: Service Convenience; Price Fairness; Customer Satisfaction; Customer Loyalty.